Design, Optimization And Performance Profiling Of Flexible Nano-vesicular Ciprofloxacin Gel: A Targeted Therapy For Ocular Bacterial Keratitis - Satyam Khajuria; Pritpal Kaur Malhi; Ramandeep S Narang; Karanpreet Kaur; Jasjeet Kaur Narang (Fabad Journal of Pharmaceutical Sciences, 2026)
Bacterial keratitis (BK) constitutes a severe eye infection capable of causing substantial vision loss, leading to ulceration and Inflammation. BK is major cause of corneal blindness in developing countries, faces challenges from the eye's protective structures, limiting drug bioavailability from conventional forms. To address the limitations of conventional dosage forms and to enhance drug efficacy, ciprofloxacin loaded nano-vesicular carriers were developed and then integrated into an optimized agent to induce gelling (Carbopol 940) for prolonging the time of contact of the drug with the eye. The prepared ciprofloxacin loaded flexible nano-vesicular carriers and gels (F40.4% w/v, F40.6% w/v, F40.8% w/v and F41% w/v) were evaluated for % entrapment efficiency, vesicle shape, in vitro drug release and, release kinetics, vesicle size, zeta potential, polydispersity index, isotonicity, sterility, degree of deformability, pH, homogeneity and grittiness, rheology, drug content, ex vivo permeation, flux, permeation coefficient, % drug retention, toxicity study, bioadhesion study, cytotoxicity studies and antimicrobial activity. Optimized formulation F4 and gel (F41%w/v) showed maximum entrapment efficiency (99.94±0.009%), particle size (275.0±0.01nm), PDI (0.272±0.001), zeta potential (−44.3±0.1 mV), spherical shape, isotonicity with blood, sterility, and high deformability, pH 7.0±0.01, drug content 98.5±3.9%, dynamic viscosity 3809mPa·s, high spreadability, in vitro release 80.5±0.32 %, ex vivo permeation 72.27±0.65%, significantly higher (p≤0.05) flux, permeability coefficient, drug retention, bioadhesion time, and antimicrobial activity than drug solution gel, with low toxicity and stability. The formulated flexible nano-vesicular ciprofloxacin gel was postulated to be promising choice for the treatment of Bacterial Keratitis( BK).